Oral Health Status of Residents in Jiangsu Province, China: An Epidemiologic Survey - Tingting Fu; Yiran Liu; Jiaping Shen; Hong Shen (Elsevier, 2022)
Introduction: This study was conducted to characterise the oral health conditions of residents in Jiangsu Province, China. Methods: In this descriptive study, 5 groups of participants were selected by a multistage stratified equal capacity random sampling, including 3- to 5-year-olds, 12- to 15-year-olds, 35- to 44-year-olds, 55- to 64-year-olds, and 65- to 74-year-olds. The data were collected by using the fifth edition of Oral Health Surveys-Basic Methods recommended by the World Health Organization (WHO). Results: In these 5 groups, the mean DMFT/dmft of coronal caries were 3.07, 0.69, 4.03, 7.15, and 11.97, respectively, resulting in prevalence rates of 59.69%, 34.98%, 52.05%, 56.86%, and 72.19%, respectively. However, the filling rates were low in all age groups (1.88%, 17.53%, 29.88%, 16.13%, and 19.36%, respectively). Only 3.58% of the 12-year-old participants had good pit and fissure sealants. The adults include three groups, 35- to 44-year-olds, 55- to 64-year-olds, and 65- to 74-year-olds, and the prevalence rates of clinical attachment loss (CAL ≥4 mm) were 32.19%, 76.47%, and 85.43%, respectively. The proportions of adult groups with implant dentures, fixed dentures, removable partial dentures, complete dentures, and substandard dentures were 0%, 26.44%, 11.11%, 0.67%, and 4.89%, respectively. Additionally, 49.64% of adults had missing teeth that were not replaced. Conclusions: Dental caries and periodontal disease were frequent and common in Jiangsu, China. But only a few of the residents sought treatment. Oral diseases continued to be a major problem for local residents.